UZBEK NATIONAL MUSIC LAMENTS, MUSES, DECORATIONS AND WAYS TO INTRODUCE THEM TO YOUNG STUDENTS - Kuziyev Islom Rustamovich (Western European Studies, 2024)
Uzbek national music is a lively tapestry of melodies and rhythms that reflect the rich cultural heritage of the Uzbek people. Acquainting young students with these aspects of Uzbek music can awaken their passion for music, deepen their understanding of cultural diversity, and nurture their creativity. This article provides information on how to instill in young students the laments and songs characteristic of Uzbek national music.
Keywords: Uzbek national music; melody; rhythm